Phase offset analysis of asymmetric communications infrastructure in smart grid - Hasan, Mohammad Kamrul; Yusoff, Siti Hajar; Ahmed, Musse Mohamud; Hassan Abdalla Hashim, Aisha; Ismail, Ahmad Fadzil; Islam, Shayla (Kauno Technologijos Universitetas, 2019)
Synchrophasor advancement has the conversant to the smart grid applications, which is turned into necessary integral parts of digital communication frameworks that include transmission of electrical signals measured crosswise over various parts, which synchronized the grid applications utilizing external precise time source. The existing Communication protocol IEC 61850 for substation automation in Smart Grid today is being used with the support of up to 12 RS232/485 and 6 Ethernet ports, SCADA server, and PMUs. However, there is still having timing and control issue in the digital smart grid applications. Therefore, this paper proposes the hybrid synchronization scheme. The design considerations of the proposed scheme are mainly IP enabled broadband connectivity, IEEE 1588 clock server, and C37.118 functionalities. The result shows that the proposed scheme performs better than the existing systems.